Peningkatan perekonomian desa melalui pengolahan kripik tomat bagi Wanita Tani di Desa Curio Kabupaten Enrekang - Nurwani; Ihlazul Amal; Wahida Hi. Amier; Muliati; Sumardi; Ayu Lestari; Nurul Fadillah; Muh. Nurdiansyah; Ferdyansyah; Aslam Arya Wiranugraha; Nur Afni Asnia; Fadillah Pratiwi S; Suherman (Jurnal Dedikasi Masyarakat, 2023)
Curio Village, Enrekang Regency, stands out as having high economic potential in the horticulture sector, focusing mainly on vegetable crops, especially tomatoes. This research aims to understand the economic situation of women farmers in Curio Village, especially in terms of tomato production and marketing. The advantage of this village lies in the typographic and climatic conditions that support the fertile growth of tomato plants. Identification of potentials and obstacles was carried out to detail the challenges faced by farmers, especially those related to the processing and marketing of tomato products. The research results show that processing tomato chips is a concrete solution to price fluctuations and product storage difficulties, positively impacting the economy of women farmers and the Curio Village community as a whole. The emphasis on plastic packaging based on practicality and visual appeal strengthens the marketing aspect of the product. This activity's success can guide the development of micro, small, and medium enterprises (MSMEs) and support women's empowerment in the agricultural environment.